Pesan Akhlak dalam Novel Gadis di Kamar Hotel - Iin Meriza (ISTIFHAM, 2023)
The novel Gadis di Kamar Hotel (Girl in a Hotel Room) by Airin Ahmad, which was initially posted on a Facebook group, Group Komunitas Belajar Menulis (KBM), received many negative responses besides positive responses. Netizens were misled by the title that they thought the novel contained pornography. However, the preconception is reversed when the reader reads the entire contents of the novel, and there are lots of moral messages as taught in Islam. In this article, the author wants to look in detail at the message of Islamic morality in the novel using the library research method. In the data analysis, the author used the method of content analysis. The results of this study indicate that the message of morality in the novel Gadis di Kamar Hotel includes morals towards Allah such asmahabbah, ridha, raja, khauf, and shabr; as well as morals towards others, including iffah (avoiding sins), 'adil (being proportional and not tyrannical), husnudzan (thinking positively toward others), being generous, shiddiq (being honest) and rahmah (being compassionate).